Implementation of Digital-Based Learning Media on Thematic Material on Students’ Scientific Abilities - Mansur, M.; Nurwahidin, Muhammad; Herpratiwi, Herpratiwi (UNDIKMA, 2024)
Learning applied to elementary school-age children is very crucial, because the methods and processes of teaching teachers seem to force students to be able to achieve predetermined competencies. This research uses the (SLR) method. regarding research methods: